Persistent left superior vena cava: A challenge for permanent pacemaker implantation - Abraham Speedie; Cinosh Mathew; Rajneesh Calton (Wolters Kluwer Medknow Publications, 2016)
Persistent left superior vena cava is the most common variation in the anomalous venous return to the heart. It is usually asymptomatic and discovered incidentally during imaging and the aberrant position of a pacemaker lead, central venous catheters, or retrograde cardioplegia for cardiac surgery. We present two different approaches of pacemaker implantation in this congenital anomaly.